Ovarian activity and postpartum reproductive performance of dual-purpose cows with and without supplementation in the subhumid tropics of Mexico - Armenta-Carmona, Julia (2022)
The aim of this study was to characterize the ovarian activity and postpartum reproductive performance of grazing dual-purpose cows with and without supplementation. In total, 30 Bos taurus x Bos indicus multiparous cows in the central zone of the state of Yucatán, Mexico were used. Body weight and body condition score (BCS) were recorded weekly, and the ovaries were monitored by ultrasound every other day. The number and diameter of the follicles were recorded, as well as the presence or absence of a corpus luteum (CL). Only the presence of large follicles (>10 mm) was considered. Ovarian activity was defined as the calving to first dominant follicle interval (IPPF), the residence time of the first dominant follicle (TPPF), the number of dominant follicles before the first oestrus (NFDAE) and before the first CL (NFDACL), and the reproductive performance as calving to first oestrus interval (IPPE), the calving to first CL interval (IPPCL) and the pregnancy rate (PT). The effect of supplementation was significant for body weight loss and CC, TPPFD, IPPE (p<0.05). Feed supplementation mitigated body weight and BCS losses but had minimal effect on ovarian activity and postpartum reproductive performance.